A remarkable moss-mimicking new species of genus Pericentrus (Phasmatodea: Lonchodidae: Lonchodini) from Xizang, China, with significantly reduced antennal length - Gao, Hao-Ran; Wu, Chao; Li, Ya-Jin (Zootaxa, 2026)
A remarkable moss-mimicking new species, Pericentrus cryptopetalus sp. nov., is described from Xizang, China. This species exhibits a marked reduction in antennae length relative to its congeners. An updated key to the females of this genus is provided, and hypotheses regarding the antennae reduction are discussed. The type specimens are deposited in Yunnan Agricultural University (YNAU).